The Fixer - Piot, Charles (Theory in Forms, 2019)
In the West African nation of Togo, applying for the U.S. Diversity Visa Lottery is a national obsession, with hundreds of thousands of Togolese entering each year. From the street frenzy of the lottery sign-up period and the scramble to raise money for the embassy interview to the gamesmanship of those adding spouses and dependents to their dossiers, the application process is complicated, expensive, and unpredictable. In The Fixer Charles Piot follows Kodjo Nicolas Batema, a Togolese visa broker-known as a "fixer"-as he shepherds his clients through the application and interview process. Relaying the experiences of the fixer, his clients, and embassy officials, Piot captures the ever-evolving cat-and-mouse game between the embassy and the hopeful Togolese as well as the disappointments and successes of lottery winners in the United States. These detailed and compelling stories uniquely illustrate the desire and savviness of migrants as they work to find what they hope will be a better life.